Strengthening the Implementation of the Police Personality Code of Ethics through Religious Character-based FGDs at the Medan Police Headquarters - Rozali, M.; Kharomah, Larasati Nur; Hairiyati, Jamiah; Prandana, Arya (Sarana Ilmu Indonesia (salnesia), 2025)
Focus Group Discussions (FGDs) can serve as an effective platform to explore members’ understanding of the code of ethics, identify challenges, and formulate reinforcement strategies aligned with religious values. This community service activity was carried out in April 2025 at the Headquarters of the Medan City Police, aiming to strengthen the Code of Ethics of the Indonesian National Police (POLRI) among its members. By utilizing FGDs focused on religious character, this initiative addressed the potential erosion of ethical compliance due to work pressure and complex environments. Religious values were regarded as a strong moral foundation. The program included problem identification, planning, participatory FGD sessions with religious-based materials and case studies, and impact evaluation. The results showed improved understanding of the code of ethics and the relevance of religious character, evidenced by enhanced ethical dilemma analysis, increased commitment to religious values, and more proactive problem-solving. Active participation and positive feedback confirmed the members’ readiness for self-reflection and heightened motivation to implement the code of ethics and religious values.